Impact Of Mind Sound Resonance Technique On Work-Related Flow Inventory And Sleep Quality Among Enthusiast Kathak Dancers From Different Professional Backgrounds - Chakraborty, Rama; Babu, Natesh; Chakraborty, Prasun (International Research Journal of Ayurveda & Yoga, 2024)
BackgroundKathak is one of the most popular Indian classical dance forms. Working professionals out of passion enjoy kathak dance but due to work engagements and reduced sleep quality, discontinue the practice of Kathak. Mind Sound Resonance Technique has been proven to improve sleep quality. Investigation among practitioners of Khatak is low and the literature survey supports the basis for this study. The present research aims to explore the influence of MSRT on the work-life inventory and sleep quality among Kathak dancers who are working professionals.ObjectivesThe objective of the study is to assess the potential benefits of enhancing work enjoyment and sleep quality of Kathak dancers from different professional backgrounds through applications of Mind Sound Resonance Techniques.MethodsA single group pre-post study on (N=29) working professionals trained in Kathak were conveniently selected for the study. MSRT was imparted to all the participants for 20 minutes, per two times for 12 weeks. The pre and post-assessments were done on work-life inventory, job satisfaction, absorption, work enjoyment, and intrinsic work motivation using the Work-Related Flow Inventory (WOLF) and sleep quality using the Pittsburgh Sleep Quality Index.ResultsCronbach alpha measuring the reliability score of WOLF was (α = 0.8). Within-group analysis the total score of work-life balance and sleep quality was found to be statistically significant from pre- to post (p<.001).ConclusionThe results indicate improvement in various domains of work-related flow inventory and sleep quality. Thus, rejecting the null hypothesis. We conclude that the Yogic relaxation technique employed in this study attunes the body-mind system to be relaxed and practitioners can bring a balance in their work-life and pursue their interests and passion to lead a fulfilled life.